FORMULATION DEVELOPMENT, EVALUATION AND OPTIMIZATION OF MEDICATED LIP ROUGE CONTAINING NIOSOMAL ACYCLOVIR FOR THE MANAGEMENT OF RECURRENT HERPES LABIALIS - V., Rajalakshmi S.; G., Vinaya O. (International Journal of Applied Pharmaceutics, 2017)
Objective: Aim of the study was to formulate, evaluate and optimize medicated Lip rouge containing acyclovir encapsulated inside a novel vesicular carrier, niosome so that the formulation can improve its membrane penetration. Formulating as a cosmetic Lip rouge formulation will also improve patient compliance in the treatment of herpes labialis. Methods: Acyclovir niosomes were prepared by thin film hydration method. Niosomes were evaluated and were optimized by considering the entrapment efficiency and in vitro release profile. The optimized niosomes were incorporated into lipstick, lip balm and lip rouge for selecting the best lip formulation. Based on the in vitro release profile, ease of application and properties of prepared formulations lip rouge was selected and further evaluations were carried out. Results: Among the six formulations of niosomes NF2 has showed 88.49 % entrapment efficiency and 86.97% cumulative drug release in 8 h. The formulation was optimized considering both entrapment efficiency and in vitro release. The optimized formulation of niosomes was incorporated into Lipstick, lip balm and lip rouge. The evaluation results of lipstick, lip balm and lip rouge for in vitro release suggested lip rouge as the best formulation. The percentage cumulative release of drug from optimized lip rouge at the end of 8 h was 84.77%. The percentage cumulative drug release in ex vivo studies for 8 h was 60.88 %. Conclusion: The results suggested that prepared lip rouge containing acyclovir niosomes can effectively deliver the drug than the marketed acyclovir cream and successful therapy of Recurrent Herpes labialis can be achieved.